Productive performance of alfalfa (Medicago sativa), Caravelí variety, subject to grazing in the Huaral valley - Bazán R., Víctor (2017)
The dry matter (DM) production of alfalfa (Medicago sativa), Caraveli variety, was evaluated per cut and per year, and its persistence over time in a prairie of the IVITA-Huaral Station of the Faculty of Veterinary Medicine, San Marcos University (Lima, Peru). The pasture was installed in the spring of 2011 in 1 ha of land in beds of 3 x 40 m, using the method of hand sowing (35 kg/ha). Irrigation was performed periodically. The cultivation was grazed with dairy cows, from the third cut when it presented 10% flowering. A total of 28 cuts were done between December 2011 and November 2014. The DM in the first, second and third year had a mean per cut of 373.3, 395.0 and 409.6 g/m2, respectively (p<0.05). The number of plants per area decreased significantly within year (p<0.05), without affecting the production of dry matter.